2007
DOI: 10.1016/j.neuroimage.2007.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic response function in patients with stroke-induced aphasia: Implications for fMRI data analysis

Abstract: Functional MRI is based on changes in cerebral microvasculature triggered by increased neuronal oxidative metabolism. This change in blood flow follows a pattern known as the hemodynamic response function (HRF), which typically peaks 4-6 s following stimulus delivery. However, in the presence of cerebrovascular disease the HRF may not follow this normal pattern, due to either the temporal signal to noise (tSNR) ratio or delays in the HRF, which may result in misinterpretation or underestimation of fMRI signal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
147
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(158 citation statements)
references
References 19 publications
9
147
2
Order By: Relevance
“…In patients with stroke it has been shown that the HRF can be altered, which may result in misinterpretation or underestimation of fMRI signal. 17,18 The only way to disentangle vascular from neural impairment-driven changes in the BOLD response is to also use stimuli that are performance matched, thereby using similar neural and cognitive resources.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with stroke it has been shown that the HRF can be altered, which may result in misinterpretation or underestimation of fMRI signal. 17,18 The only way to disentangle vascular from neural impairment-driven changes in the BOLD response is to also use stimuli that are performance matched, thereby using similar neural and cognitive resources.…”
Section: Introductionmentioning
confidence: 99%
“…After 1s, this changed to a black cross (84 point font) which remained visible until the start of the next trial/event as detailed in Figure 2. A long inter-trial interval (jittered between 10-18s, mean 14s) was employed to allow for the delayed hemodynamic response function observed with stroke patients (Bonakdarpour et al, 2007;Meinzer, Lahiri, Flaisch, Hannemann, & Eulitz, 2009) and to enable future comparison with a planned companion study on individuals with post-stroke aphasia. Order of presentation within each run was pseudorandomised with no more than four items from any one condition (concrete real words, abstract real words and pseudowords) being presented in succession and never more than four words or pseudowords in a row.…”
Section: Methodsmentioning
confidence: 99%
“…An inter-trial interval (jittered between 10-18s, mean 14s) followed each auditory stimulus presentation. The long interval was designed to allow for future comparison of this data with that of patients with post-stroke aphasia, who can experience a delay in hemodynamic response function (Bonakdarpour et al, 2007). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations